STUDI TENTANG KESEJAHTERAAN MASYARAKAT DALAM PERSPEKTIF EKONOMI ISLAM - Farida Z Fatma; La Ode Muh. Harafah; Baheri Baheri (Universitas Halu Oleo, 2022)
This study aims to analyze the welfare of society in the perspective of Islamic economics. Prosperity in the Islamic economy is based on the concept of maqasid sharia, namely fulfilling the needs of Dharuhiyyat, Hajiyyat and Thasiniyat. The primary data source uses a questionnaire. The population is 613 people with a sample of 86 respondents. Data analysis used quantitative descriptive analysis. The results showed that the need for dharuhiyyat assessment based on religious preservation (X1) had an average score of 3.69 (74%) which was in the good category. Mental needs (X2) with an average score of 1.77 (44%) are in the pretty good category. The need to maintain (X3) has an average score of 6.23 (89%) in the very good category. Hereditary needs (X4) have an average score of 2.53 (84%) in the very good category. Property needs (X5) have an average score of 2.98 (99%) in the very good category. The average score for meeting the needs of daruhiyyat is 78 percent, meaning that the fulfillment of the needs of daruhiyyat is well met.